The Climate Security Sensitivity Tool (CSST) - Sarzana, Carolina (2023)
The Climate Security Sensitivity Tool (CSST) is an ex-ante programming assessment tool for conflict-sensitive and peace-responsive climate action, encompassing all production systems including livestock ones. The CSST supports practitioners and decision-makers developing adaptation initiatives in avoiding maladaptation and its associated unintended consequences, avoiding conflict relapses, and contributing to peacebuilding.